Evidence of the photosynthetic origin of monoterpenes emitted by Quercus ilex L leaves by C-13 labeling - Loreto, F; Ciccioli, P; Cecinato, A; Brancaleoni, E; Frattoni, M; Fabozzi, C; Tricoli, D (PLANT PHYSIOLOGY, 1996)
The carbon of the four main monoterpenes emitted by Quercus flex L. leaves was completely labeled with C-13 after a 20-min feeding with 99% (CO2)-C-13. This labeling time course is comparable with the labeling time course of isoprene, the terpenoid emitted by other Quercus species and synthesized in leaf chloroplasts. It is also comparable with that of phosphoglyceric acid. Our experiment therefore provides evidence that monoterpenes emitted by Q. ilex are formed from photosynthesis intermediates and may share the same synthetic pathway with isoprene. By analyzing the rate and the distribution of labeling in the different fragments, we looked for evidence of differential carbon labeling in the alpha-pinene emitted. However, the labeling pattern was quite uniform in the different fragments, suggesting that the carbon skeleton of the emitted monoterpenes comes from a unique carbon source.
APS
Keywords: alpha-pinene; C-13 labeling; Emissions; isoprene; Monoterpenes; Quercus flex L.; Quercus ilex